'Let's Get a Bit of Context': Fifty Shades and the Phenomenon of 'Pulling to Publish' in Twilight Fan Fiction. Issue 1 (August 2014) - Brennan, Joseph; Large, David
The publishing success of E.L. James' Fifty Shades of Grey, a series with origins as Twilight fan fiction, has energised popular interest in the practice of writing fan fiction (or 'fanfics'). Equally, however, the series' popularity has fuelled debate on the ethics of its commercial publication. This article highlights the divisive and polarising phenomenon of 'pulling to publish' in the Twilight fandom. 'Pulling to publish' refers to the process of rewriting and republishing for profit a work that was inspired by another's intellectual property, and collaboratively edited by unpaid volunteers – the majority of whom would have expected the edited work to be freely available in perpetuity. Among other relevant case studies, this article examines a critical instance of pseudonymous online protest, challenge and defence between James and another well-known fanfic writer, coinciding with the March 2011 announcement that Fifty Shades would be commercially published. Several critiques of fanfic commercialisation are contextualised by a critical reading of the 'official' publication history of Fifty Shades, revealing the incompatibility of two self-constructed fan identities: the faithful and the opportunistic.